2021
DOI: 10.1002/jrs.6067
|View full text |Cite
|
Sign up to set email alerts
|

Laser‐induced phonon and magnon properties of NiO nanoparticles: A Raman study

Abstract: In the present study, the influence of laser intensity on phonon and magnon properties of nickel oxide (NiO) nanoparticles were extensively studied using room temperature Raman spectroscopy. The required NiO nanoparticles were synthesized using a simple sol–gel method. The structural and morphological properties were characterized using powder X‐ray diffraction (XRD), field emission scanning electron microscopy (FE‐SEM), and transmission electron microscopy (TEM) techniques. The rarely reported surface optical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 54 publications
1
7
0
Order By: Relevance
“…The Raman peaks at 355 and 515 cm À1 can be ascribed to the NiO vibrational first-order phonon (1 P) modes including transverse optical (TO) and longitudinal optical (LO) modes, while the peaks at 673, 837, and 1063 cm À1 correspond to the secondorder phonon (2 P) modes 2P TO , 2P TOþLO , and 2P LO . [38,39] XPS analyses were also performed to acquire the elemental valence and chemical composition at the surfaces of the samples. Figure 6a shows the XPS full-survey spectra of PANC, FOCNF, and NOCNF.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The Raman peaks at 355 and 515 cm À1 can be ascribed to the NiO vibrational first-order phonon (1 P) modes including transverse optical (TO) and longitudinal optical (LO) modes, while the peaks at 673, 837, and 1063 cm À1 correspond to the secondorder phonon (2 P) modes 2P TO , 2P TOþLO , and 2P LO . [38,39] XPS analyses were also performed to acquire the elemental valence and chemical composition at the surfaces of the samples. Figure 6a shows the XPS full-survey spectra of PANC, FOCNF, and NOCNF.…”
Section: Resultsmentioning
confidence: 99%
“…The Raman peaks at 355 and 515 cm −1 can be ascribed to the NiO vibrational first‐order phonon (1 P) modes including transverse optical (TO) and longitudinal optical (LO) modes, while the peaks at 673, 837, and 1063 cm −1 correspond to the second‐order phonon (2 P) modes 2P TO , 2P TO+LO , and 2P LO . [ 38,39 ]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…44,45 Although the 2 M interaction is difficult to be observed in an antiferromagnetic material, 45 the 2 M band in NiO has been widely studied and its dependences with size, temperature, and defect structure, among other parameters, have been well established. [46][47][48] This band, which indicates the existence of an antiferromagnetic order in NiO, 48 arises from superexchange interactions between the next-nearest-neighboring Ni 2+ ions (NNN) in the Ni 2+ − O 2− −Ni 2+ linear atomic chain, 48,49 and in nanostructures, its existence is very sensitive to the presence of point defects. 49 For example, it has been recently reported that Cu 2+ inclusion in NiO nanoparticles results in a decrease in the intensity of the 2 M band, 50 and for bulk NiO film, it has been reported that the absence of the 2 M band responds to phenomena related to a high density of point defects that interfere with the NNN superexchange interaction.…”
Section: Resultsmentioning
confidence: 99%
“…Although the 2 M interaction is difficult to be observed in an antiferromagnetic material, 45 the 2 M band in NiO has been widely studied and its dependences with size, temperature, and defect structure, among other parameters, have been well established 46–48 . This band, which indicates the existence of an antiferromagnetic order in NiO, 48 arises from superexchange interactions between the next‐nearest‐neighboring Ni 2+ ions (NNN) in the Ni 2+ − O 2− −Ni 2+ linear atomic chain, 48,49 and in nanostructures, its existence is very sensitive to the presence of point defects 49 .…”
Section: Resultsmentioning
confidence: 99%